Visuals to Ideologies: Exploring the Linguistic Landscapes of Mindanao State University Marawi Campus - Abbas, Juhaid H.; Samad, Binnor M. Abdul; Imam, Mohammad Hussein M.; Berowa, Annie Mae C. (Lingua Cultura, 2022)
The research demonstrated the linguistic landscapes of the Mindanao State University Marawi Campus in the Southern Philippines, known as the “Melting Pot of the South”, where multilingualism, multiculturalism, and multimodality were quite situated. Linguistic Landscape (LL) encompassed and manifested the range of language use in society. Under the theoretical lens of linguistics, the research aimed to qualitatively and descriptively illustrate the linguistic tokens that marked the context of the school community. The needed data were photographed and collected inside the university premises and analyzed in terms of the number of languages used, language choice, and types of signs. The research reveals a sociolinguistic paradox: the multilingual realities of the school community and the prevalent exhibitions of monolingual English on its linguistic landscapes, which consequently seems to dishearten the status, propagation, promotion, and/or effectivity of multilingual policies and education in the Philippines. Furthermore, the research provides theoretical and practical contributions. Theoretically, it shows another lens of the notion of presumed language prestige and hierarchies. Furthermore, practically, it aids the deepening of knowledge and understanding of language use, and its implications, in public spaces. Finally, the research suggests revisiting and recalibrating the exhibition of multilingualism in the country by simply considering the status of language use in their environments, as they do not just reflect or manifest languages but also propagate and promote them.